Predietary Counseling in Ketogenic Diet: The 5R Model - Rosha, Rahul; Singla, Rajiv; Kalra, Bharti (Journal of Social Health and Diabetes, 2018)
A major determinant of success while following a ketogenic diet is the counseling that precedes and accompanies the dietary advice. Effective predietary counseling lays a strong foundation upon which successful outcomes can be built. Predietary counseling, an art as well as a science, is best understood through a bio-psychosocial viewpoint. This brief communication shares an alliteratively named model, the 5R rubric. Rapport, realistic realization, reliability, readiness to change, and relationship must be explored and improved during the process of counseling. These five R's remind one to practice continuous, holistic counseling, without forgetting any of the factors that may impact outcomes. Pre-ketodietary counseling is a theranostic intervention, as it helps in both assessment (diagnosis) and improving outcomes (therapeutics).
Keywords: Atkin's diet; diabetes; ketogenic diet; medical nutrition therapy; obesity; weight loss